Evaluation of body weight prediction Equations in growing heifers - Marcia de Oliveira Franco; Marcos Inácio Marcondes; José Maurício de Souza Campos; Denise Ribeiro de Freitas; Edenio Detmann; Sebastião de Campos Valadares Filho (Acta Scientiarum. Animal Sciences, 2017)
This study was realized to evaluate prediction models for body weight (BW) using body measurements as heart girth (HG), wither height (WH), hip width (HW), body length (BL) and hip height (HH), and develop new Equations to predict the BW of Holstein and crossbred heifers. Prediction Equations (1, 2, 3, 4, 5 and 6) proposed in previous studies were tested, while body measurements, which were more significant in terms of predicting BW, were used to obtain new Equations. Heart girth was the body measurement with the greater correlation with BW. Equation 4 presented the best prediction results, showing a low average deviation, high accuracy and precision. Equations 1 and 2 predicted with a high presence of bias, while 2 had the lowest value of the concordance correlation coefficient and a great contribution made by systematic error. The 3 model presented a high variability in predicting BW. For both Holstein and crossbred heifers, the Equations evaluated are inadequate for predicting BW. Among the Equations evaluated, the model using HG presented the best adjustment and the greater adjusted coefficient of determination. Body measurements relating to HG and BL were the most significant variables in predicting the BW, resulting in the following Equation: BW = - 372.89 + 2.8072 × HG + 1.6087 × BL.